Continuous cultivation of Chlorella minutissima 26a in a tube-cylinder internal-loop airlift photobioreactor to support 3G biorefineries - Tagliaferro, Geronimo Virginio; Izario Filho, Helcio Jose; Chandel, Anuj Kumar; Silva, Silvio Silverio da; Silva, Messias Borges [UNESP]; Santos, Julio Cesar dos (Elsevier B.V., 2019)
Microalgae Chlorella minutissima 26a was cultivated in a tube-cylinder internal-loop airlift photo-bioreactor under continuous cultivation conditions. The goal was to investigate the influence of different nitrate levels on the growth and composition of microalgae. Three nitrate concentrations (75, 150 and 225 mg L-1) were assessed under a fixed flow rate and the outlet flow was analyzed for concentration of biomass, lipid, carbohydrate and protein. Nitrate concentration at higher level (225 mg L-1) in the medium promoted biomass growth (188.6 mg L-1 d(-1)) and lipid production (92.8 mg L-1 d(-1)), and decreased carbohydrate amount (29.1 mg L-1 d(-1)) without any change in protein content (37.7 mg L-1 d(-1)). Use of tube-cylinder internal-loop airlift photobioreactor in continuous mode could be a promising approach in algal biorefineries so called 3G biorefineries, resulting in high biomass productivity in a simple cultivation system. (C) 2018 Published by Elsevier Ltd.
Keywords: Chlorella minutissima; Continuous microalgae cultivation; Tube-cylinder internal-loop airlift; photobioreactor; 3G biorefineries; Nitrogen repletion effect